KEPUNAHAN LEKSIKON UPACARA KELEMAN SEBAGAI KEARIFAN LOKAL KAMPUNG BONGSO WETAN GRESIK - Dewanto; Yeni Probowati (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This research was conducted to find out to what extent the level of the kelemen ceremony is being begun to experience extinction in Bongso Wetan Menganti Gresik village. The extinction of the lexicon was caused as a reason for conducting research to find out the loss and shifting of the ancestral culture of people of Madurese ethnic descents. The main factors are internally and externally from the local community. This study used a qualitative approach with the theoretical perspective of Alfred Schutz. The selection of the location for this study used a purposive technique, namely the people of Madurese ethnic descents from generation to the next generation. The villagers perform ceremonies have lasted hundreds of years. The study in which used in this reserach is called as Culture. The tradition of the Keleman ceremony is one of the cultures that has been being running in the village community which is of Madurese ethnic descents. Keywords: Keleman, culture, tradition, Madura, and descent